An Analysis of Character Education Values in Year 11 Highschool English Textbook - Nurindah Purnama Sari; Maemuna Muhayyang; Chairil Anwar Korompot (Journal of Excellence in English Language Education, 2022)
This study aims to describe the values of character education in the English textbooks of Class 11 Senior High School. The data in this study are in the form of texts containing the value of character education. The data source of this research is the class XI senior high school English books curriculum 2013. There are two data collection techniques used in this study, namely the reading technique and the note-taking technique. Then, the data analysis technique in this study went through three stages, namely (1) reduction, (2) presentation, and (3) drawing conclusions. In addition, the data validity checking technique was carried out, namely discussions with experts in assessing the results of data analysis so that all findings in this study can be justified. The results of this study found that there are 14 values of character education, namely the values of religious, honest, disciplined, diligent, creative, independent, nationalism, appreciation, communicative, peace-loving, intellectual, beauty, sympathy, and loyal character values which are implemented through text sentences and images. It can be concluded that the 11th-grade high school English textbook only has 14-character education values. There are 4 values that are not found in the textbook, which include the values of tolerance, curiosity, democracy, and love for the homeland.